2012
DOI: 10.1080/14680777.2012.741872
|View full text |Cite
|
Sign up to set email alerts
|

Women, Smartphones and the Workplace

Abstract: This paper explores the ways that a sample of professional women use smartphones to manage their personal activities and work responsibilities. It reveals a number of specific, mindful practices used to convey and enable accessibility, professionalism and responsiveness to colleagues and clients, showing how smartphones are used to shape and maintain professional identities. At the same time, women also choose to set boundaries to ensure that the immediacy enabled by their smartphones does not encroach upon th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Almost all research findings confirm the contradictory impact of mobile technology on work-life balance: While widespread use of mobile technology facilitates the coordination of various tasks, there is a danger of employees active in knowledge intensive sectors being engaged with work not just anywhere and anytime but more like everywhere and all the time (Crowe & Middleton, 2012;Dén-Nagy, 2014;Kossek, 2016;Towers, Duxbury, Higgins, & Thomas, 2006;Wajcman, Rose, Brown, & Bittman, 2010).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Almost all research findings confirm the contradictory impact of mobile technology on work-life balance: While widespread use of mobile technology facilitates the coordination of various tasks, there is a danger of employees active in knowledge intensive sectors being engaged with work not just anywhere and anytime but more like everywhere and all the time (Crowe & Middleton, 2012;Dén-Nagy, 2014;Kossek, 2016;Towers, Duxbury, Higgins, & Thomas, 2006;Wajcman, Rose, Brown, & Bittman, 2010).…”
Section: Introductionmentioning
confidence: 81%
“…A survey exploring the smartphone use of Canadian professional women working long hours revealed that the respondents used phones to manage family and work related tasks simultaneously, and they were mindful of the need to be available outside of working hours (Crowe & Middleton, 2012). They regularly checked their e-mail to show responsiveness and responsibility for their colleagues' work.…”
Section: Special Effects Of Motherhoodmentioning
confidence: 99%
“…Existing literature holds many examples of how people occupying various social positions strategically limit or qualify their mobile media use. For example, to keep professional and personal duties separate, working women may choose to check their phones when out of the office at certain times only, with some even physically hiding their phones away in drawers while attending to their children (Crowe & Middleton, 2012).…”
Section: Contextual (Non-)use Vs Absolute Non-usementioning
confidence: 99%
“…Smart home technologies also support the extension of work and its monitoring into the home. There is a large body of literature that addresses the role of computer networked technologies in the intensification of work and collapse of work-life boundaries (Crowe and Middleton, 2012; Green, 2003). Researchers of labour processes at the height of the office automation movement in the 1980s identified the dynamic of visible versus invisible labour as central in the design of computer technologies (Suchman, 1995; Star and Strauss, 1999).…”
Section: Exterioritiesmentioning
confidence: 99%